Legal Protection for Foreign Workers in Indonesia: Opportunities and Challenges (International Journal of Scientific Research and Management (IJSRM), 2020)
The impact of globalization and the current free market in the form of movement of investment, capital and labor between countries is unavoidable. Indonesia, as a member of the World Trade Organization (WTO), opens up opportunities for investment and foreign workers to run its business. The purpose of this research is to find out about legal protection for foreign workers in Indonesia as regulated by the 1945 Constitution and various other laws and regulations. This study uses a qualitative approach that is normative juridical, and the specification of the analysis of this research is carried out descriptively. The results show that the provisions regarding foreign workers in Indonesia still have many obstacles, especially in promoting investment, creating new regulatory challenges that may need to be responded to by policy makers in Indonesia quickly, and the right strategy is needed in the field of using foreign workers. although Law No. 11 of 2020 has been passed and optimizes the role of non government organizations (NGOs) as assisting institutions for foreign workers to increase awareness of human rights in Indonesia